INVESTIGATION OF TASK SCHEDULING IN GRID - A. A. Prihozhy; O. M. Frolov (Системный анализ и прикладная информатика)
The problem of execution management of client’s tasks and optimal management of cluster’s computing resources is one of the key problems in grid. In this paper the detailed investigation and comparison of task schedulers and task scheduling techniques has been performed with respect to the result quality and throughput. The results of conducted computing experiments have found out the critical scheduler’s components and preferable scheduling approaches which are promising and indicate the ways of further development of grid optimization methods.